Reproductive Health Animations as Efforts to Prevent Sexual Harassment in Deaf Students - Winarsih, Murni; Wahyuni, Lussy Dwiutami; Nanik, Umi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
This research aims to obtain information about the needs of developing reproductive health animation media to prevent sexual harassment and deviation in deaf students. The research was conducted at 14 school of special in Jakarta and West-Java Province with quantitative method.Â Data was taken from 105 teachers through a questionnaire and analyzed using Huberman and Miles models and the process including data reduction, data display, and verification. The results of this research obtain communication barriers which are the main cause of the ineffectiveness of sex education in deaf students can be overcome by developing reproductive health media for deaf students. So, it can be concluded that learning of reproductive health for deaf students provide a good understanding of sex education in reproductive health.